Efektivitas Komunikasi Penyuluh Pertanian dalam Program Pekarangan Pangan Lestari (P2L) di Kecamatan Colomadu Kabupaten Karanganyar - Muhtar, Salsabila Ayunis; Padamningrum, Dwiningtyas; Rusdyana, Eksa (Journal of Integrated Agricultural Socio-Economics and Entrepreneurial Research (JIASEE), 2024)
Pekarangan Pangan Lestari (P2L) is a program that is carried out jointly by community groups by seeking to use unproductive yards or vacant land as a place for planting. In achieving the goals of P2L there needs to be a communication process carried out by agricultural extension workers to KWT members. An indicator of the effectiveness of communication in a program is Source Credibility (source credibility), the message, and the message recipient. This study aims to examine the effectiveness of the message and the credibility of the communicator affecting the communication effectiveness of the Pekarangan Pangan Lestari (P2L) program. The basic method used is descriptive quantitative with survey techniques. Samples were taken from purposive random sampling with a total of 65 respondents. Data analysis used Multiple Linear Regression. The results showed that the effectiveness of the message and the credibility of the communicator had a significant effect on the Pekarangan Pangan Letsrai (P2L) program with a significant value of <α (0.05). This shows that the effectiveness of communication in the Pekarangan Pangan Lestari (P2L) is influenced by two variables, namely the effectiveness of the message and the credibility of the communicator.